R unning Head: Novel Recombinant Phytate - d egrading Enzyme Production Statistical Optimization of the Induction of Phytase Production by Arabinose in a recombinant E. coli using Response Surface Methodology - Abd - ElAziem Farouk; Anis Shobirin Meor Hussin; Ralf Greiner; Shareef Mohideen Ismail; Mohamed Faizal Batcha; Hamadah Mohd Nur Lubis (Universitas Gadjah Mada, 2010)
The production of phytase in a recombinant E.coliusing thepBAD expression system wasoptimized using response surface methodology with full-factorial faced centered central composite design. The ampicilin and arabinose concentrationin the cultivation media and the incubation temperature were optimized in order to maximize phytase productionusing 23 central composite experimental design. With this design the number of actual experiment performed could be reduced while allowing eludidation of possible interactions among thesefactors. The most significant parameter was shown to be the linear and quadratic effect of the incubation temperature. OPtim al conditionsfor phytase production were determinedto be100 ?g/ml ampicilin, 0.2 % arabinose and an incubation temperature of37ºC.The production of phytase in the recombinant E. coliwas scaledup to 100ml and 1000ml.